Ultrasonographic findings of feline aortic thromboembolism. Issue 12 (December 2022) - Eberlé, Olivia; Pouzot-Nevoret, Céline; Thomas-Cancian, Aurélie; Lurier, Thibaut; Nectoux, Alexandra; Ségard-Weisse, Emilie
Objectives: The aim of the study was to describe the ultrasonographic characteristics of feline aortic thromboembolism (ATE) and determine potential associations between ultrasonographic findings and prognosis. Methods: Data were retrospectively collected from the medical records (2013–2021) of cats that were diagnosed ultrasonographically with ATE based on the presence of a thromboembolus (TE) in the distal aorta beginning after the departure of the renal arteries. Results: Twenty-nine cats were included in this study. The most frequent location for an ATE was at the aortic trifurcation. The median length of TEs was 9 mm (range 3.5–42.9). TEs appeared homogeneous and isoechoic to surrounding tissues in all cases. No correlation was found between the appearance of the TE and the duration of clinical signs. The obstruction of blood flow in the distal aorta at the aortic trifurcation was complete in 66% of cases and incomplete in 34% of cases. The survival rate was significantly lower when the obstruction was complete (11%, 95% confidence interval [CI] 2–34) compared with incomplete (70%, 95% CI 35–92). The arterial wall characteristics were as follows: smooth and thin (62%), and hyperechoic (38%). Conclusions and relevance: Increased vascular obstruction of TEs was associated with a lower survival rate.